Structural Safety Evaluation of a Fairlead Chain Stopper for the Disconnectable Mooring System of Floating Offshore Wind Turbines - Youngjae Yu; Sang-Hyun Park; Youngsik Jang; Sang-Rai Cho (한국해양공학회지, 2025)
The global demand for renewable energy is increasing, with annual expansion in the installed capacity of offshore wind turbines. The increasing scale of offshore wind turbines necessitates robust and reliable mooring systems, particularly for harsh environments where disconnection is required. This study examined the structural and fatigue safety of a Fairlead chain stopper (FCS), a critical component of a disconnectable mooring system (DMS) for a 10MW floating offshore wind turbine. The FCS was evaluated under extreme load conditions using a semi-submersible platform design based on the DTU 10MW turbine. The loads were determined using the minimum breaking load (MBL) of a 147mm grade R4S mooring chain, considering the horizontal design working range (DWR) and vertical design inlet angle (DIA) for structural analysis. Fatigue analysis used the dynamic tension results from integrated load analysis processes through the Rainflow counting method to derive the tension ranges and cycle counts. The results suggested that the FCS design satisfies the DNV design criteria for the structural and fatigue strength, with safety factors exceeding the requirements under all operational scenarios considered. This confirms the suitability of the FCS for reliable and safe operation in the demanding conditions of a 10MW floating offshore wind turbine, helping advance disconnectable mooring technology.